Is reverse cholesterol transport regulated by active cholesterol? - Theodore L. Steck; Yvonne Lange (Journal of Lipid Research, 2023)
This review considers the hypothesis that a small portion of plasma membrane cholesterol regulates reverse cholesterol transport in coordination with overall cellular homeostasis. It appears that almost all of the plasma membrane cholesterol is held in stoichiometric complexes with bilayer phospholipids. The minor fraction of cholesterol that exceeds the complexation capacity of the phospholipids is called active cholesterol. It has an elevated chemical activity and circulates among the organelles. It also moves down its chemical activity gradient to plasma HDL, facilitated by the activity of ABCA1, ABCG1, and SR-BI. ABCA1 initiates this process by perturbing the organization of the plasma membrane bilayer, thereby priming its phospholipids for translocation to apoA-I to form nascent HDL. The active excess sterol and that activated by ABCA1 itself follow the phospholipids to the nascent HDL. ABCG1 similarly rearranges the bilayer and sends additional active cholesterol to nascent HDL, while SR-BI simply facilitates the equilibration of the active sterol between plasma membranes and plasma proteins. Active cholesterol also flows downhill to cytoplasmic membranes where it serves both as a feedback signal to homeostatic ER proteins and as the substrate for the synthesis of mitochondrial 27-hydroxycholesterol (27HC). 27HC binds the LXR and promotes the expression of the aforementioned transport proteins. 27HC-LXR also activates ABCA1 by competitively displacing its inhibitor, unliganded LXR. § Considerable indirect evidence suggests that active cholesterol serves as both a substrate and a feedback signal for reverse cholesterol transport. Direct tests of this novel hypothesis are proposed.